2014
DOI: 10.1002/jctb.4597
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of CO2with supported imidazolium-based ionic liquid membranes

Abstract: BACKGROUND Ionic liquids (ILs) are considered to be one of the future solutions to CO2 emission control because of their high CO2 solubility. Infiltrating ionic liquids into porous materials to prepare a supported ionic liquid membrane (SILM), could increase the absorption efficiency. RESULTS Four SILMs were prepared from imidazolium‐based ILs and PVDF microporous membranes. The CO2 absorption capacities of the SILMs were in the range of 0.88–3.64 mol mol−1, which were much higher than the solubility in ILs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The investigation of the difference in the interaction of CO 2 with the monocationic ILs and dicationic ILs was governed by the quantum chemical calculations [ 79 ]. Cao, et al [ 80 ] synthesized four SILMs from imidazolium-based ILs and PVDF microporous membranes. The results of their study have shown that the synthesized SILMs have maintained an excellent CO 2 absorption level during several cycles of absorption–desorption.…”
Section: Ionic Liquid Membranes (Ilms) In Gas Separation Processesmentioning
confidence: 99%
“…The investigation of the difference in the interaction of CO 2 with the monocationic ILs and dicationic ILs was governed by the quantum chemical calculations [ 79 ]. Cao, et al [ 80 ] synthesized four SILMs from imidazolium-based ILs and PVDF microporous membranes. The results of their study have shown that the synthesized SILMs have maintained an excellent CO 2 absorption level during several cycles of absorption–desorption.…”
Section: Ionic Liquid Membranes (Ilms) In Gas Separation Processesmentioning
confidence: 99%
“…During recent decades, ionic liquids (ILs) have emerged as new solvents in the field of gas separations owing to their outstanding properties, such as high thermal stability, negligible vapor pressures and tunable structures. [14][15][16][17][18][19][20][21][22] Therefore, the NH 3 absorption by ionic liquids has aroused interest around the world, and researchers have paid a lot of attention to the screening and designing of ILs to increase NH 3 solubility along with good desorption performance. Yokozeki 2 ] as an example and explained that hydrogen atoms of the cation played an important role in NH 3 absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the organic amine scrubbing CO 2 from flue gas process, ionic liquids (ILs) can be an alternative for CO 2 absorption and natural gas purification for their non‐volatility and lower regeneration energy consumption . The supported ionic liquid membranes (SILMs), where IL is immobilized in a porous support by capillary forces, possess ILs’ chemical stability and huge membrane contact surface to make them attractive for CO 2 capture and offer a high potential for industrial applications …”
Section: Introductionmentioning
confidence: 99%